The HUBUNGAN INDEKS MASSA TUBUH (IMT) DENGAN INTENSITAS NYERI SENDI LUTUT PADA LANSIA: LITERATURE REVIEW - HULWANA SALSABILA (Yayasan Pendidikan Medika Indonesia, 2022)
Abstract Unhealthy eating habits, lifestyle, and lack of physical activity in the elderly will experience an increase in fat mass that can lead to increases in body mass index exceed normal limit. This will cause pain in the joints, especially in joints that support heavy body loads such as the knee. This study was aimed to determine correlation between body mass index with knee joint pain intensity in elderly. The method used was the literature review which is derived from the search of research articles in several databases used certain keywords in the period of 2016-2020 years. Search for published articles on Google Scholar and Science Direct to find articles according to inclusion and exclusion criteria and then do a review. Based on 5 research articles obtained the results that the total number of respondents were 524 people and p value of < 0.05 in the whole article with the interpretation of a significant relationship between the BMI with the intensity of knee joint pain in the elderly. The results of the literature review 5 the concluded is that there is a connection between excess BMI and the intensity of knee joint pain in the elderly. It is expected that study will be beneficial for elderly in maintaining regular diet and exercise so that excess body mass index becomes normal so as to reduce the pain of the knee joint experienced. Key words: Body Mass Index, Elderly, Knee Joint, Pain Intensity, Literature Review